Pelatihan Perawatan Luka Putting Susu pada Ibu Menyusui di Ruang Nifas Puskesmas Tosiba - Yuhanah, Yuhanah; Naim, Rosani; Mutmaina, Rizka; Hijra, Hijra (Poltekita: Jurnal Pengabdian Masyarakat, 2024)
Breastfeeding is ineffective because both mother and baby have difficulty breastfeeding. Lack of knowledge about proper care and the dangers of nipple abrasions lead to complications of breast inflammation (mastitis), abscesses and even infections. Preventive efforts in optimizing breastfeeding success were carried out through nipple wound care training at the Tosiba Health Center for 35 breastfeeding mothers. The purpose of the activity is to implement the tridarma of higher education in the form of training so that the knowledge and skills of mothers in caring for nipples increase in the hope that the breastfeeding process takes place safely without complications. The service method goes through three stages, namely filling out questionnaires, discussing the material and direct practice for breastfeeding mothers. The results of the training increased knowledge from 35% to 78%, while the performance was 10% to 65%. Conclusion The science and techniques of nipple care are very important for expectant mothers and nursing mothers to maintain hygiene, strengthen nipples, reduce the risk of wounds during breastfeeding and avoid infection, as well as smooth milk production and breastfeeding babies well. Inter-related cooperation in Puskesmas as a follow-up to training, for the implementation of activities that are beneficial especially for the health of mothers during breastfeeding.